Comparison study of intraocular pressure reduction efficacy and safety between latanoprost and tafluprost in Japanese with normal-tension glaucoma - Ikeda Y; Mori K; Tada K; Ueno M; Kinoshita S; Sotozono C (Clinical Ophthalmology, 2016)
Yoko Ikeda,1,2,* Kazuhiko Mori,1,* Kaori Tada,3 Morio Ueno,1 Shigeru Kinoshita,4 Chie Sotozono1 1Department of Ophthalmology, Kyoto Prefectural University of Medicine, 2Oike-Ganka Ikeda Clinic, 3Department of Ophthalmology, Japanese Red Cross Society Kyoto Daini Hospital, 4Department of Frontier Medical Science and Technology for Ophthalmology, Kyoto Prefectural University of Medicine, Kyoto, Japan *These authors contributed equally to this work Purpose: To evaluate and compare the intraocular pressure (IOP) reduction efficacy and safety between the ophthalmic solutions 0.005% latanoprost (Lat) and 0.0015% tafluprost (Taf) in Japanese patients with normal-tension glaucoma (NTG).Methods: In this randomized nonmasked study, we prospectively enrolled 30 Japanese NTG patients who had used Lat monotherapy for more than 4 weeks, and randomly divided them into the following two groups: 1) Lat-to-Taf group (LT group) and 2) Taf-to-Lat group (TL group). At the beginning of the study, both groups were switched from initial Lat to Lat or Taf for 12 weeks, and then switched over to the other drug (crossover) for 12 additional weeks. At 0, 4, 12, 16, and 24 weeks, we evaluated each patient’s IOP, conjunctival injection, and corneal epitheliopathy score, and at 0, 12, and 24 weeks, we evaluated their eyelash changes and pigmentation of the eyelids and irises.Results: The mean IOP of the LT group (15 eyes) was 10.5, 10.6, and 11.1 mmHg, at 0, 12, and 24 weeks, respectively, whereas that of the TL group (15 eyes) was 11.7, 11.1, and 10.5 mmHg at 0, 12, and 24 weeks, respectively. No significant differences were found between the two groups and in the intragroup comparisons. Moreover, no significant differences were found between Lat and Taf in regard to the conjunctival injection score and corneal epitheliopathy score. Eyelash changes and eyelid and iris pigmentation were similar in both groups.Conclusion: The findings of this study show that Lat and Taf have equivalent efficacy and safety in Japanese patients with NTG. Keywords: latanoprost, tafluprost, normal-tension glaucoma, crossover